2008
DOI: 10.1148/radiol.2461061298
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of MR Imaging in the Diagnosis of Breast Lesions

Abstract: http://radiology.rsnajnls.org/cgi/content/full/2461061298/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
273
3
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(293 citation statements)
references
References 76 publications
6
273
3
11
Order By: Relevance
“…Using the QDA based on the change in signal intensity from 0 to 2 min and With our CAD scheme, the classification accuracy, sensitivity, and specificity were 85.6 %, 87.1 %, and 82.1 %, respectively. These results were comparable to the performance of radiologists in the context of differential diagnosis in DCE-MRI examinations [5][6][7][8][9][10]. Although the classification accuracy of our CAD scheme might have to be further improved in order to aid experienced radiologists, it could nevertheless be useful for less experienced radiologists.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Using the QDA based on the change in signal intensity from 0 to 2 min and With our CAD scheme, the classification accuracy, sensitivity, and specificity were 85.6 %, 87.1 %, and 82.1 %, respectively. These results were comparable to the performance of radiologists in the context of differential diagnosis in DCE-MRI examinations [5][6][7][8][9][10]. Although the classification accuracy of our CAD scheme might have to be further improved in order to aid experienced radiologists, it could nevertheless be useful for less experienced radiologists.…”
Section: Discussionsupporting
confidence: 67%
“…The specificity of breast DCE-MRI, which is typically between 67 and 72 %, is lower than that of mammography. Such a low specificity results in a larger number of false positives and higher biopsy rates [8][9][10]. Furthermore, DCE-MRI requires a significant amount of time for image interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Even if reported to be useful in the detection of breast carcinoma [7,8], CT has the drawback of high radiation dose levels. Contrast-enhanced MRI seems to be currently the most sensitive breast cancer detection technique [9], but have high false positive rate and still carries the burden of higher costs and lower availability.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, several experimental studies have demonstrated that quantitative methods (based on tracer kinetics modelling) can be more specific in distinguishing benign from malignant breast disease, because of the capability to derive parameters strictly related to tissue microvasculature without any operator dependency [19,[20][21][22][23][24][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. However, as there is not yet sufficient standardisation of quantitative methods, semi-quantitative approaches have been used because they could represent a compromise between qualitative and quantitative approaches.…”
Section: Discussionmentioning
confidence: 99%